Comparing the Traffic Operation, Fuel Consumption, and Pollutant Emission of Bike Lane Pattern Design with AIMSUN Microscopic Simulation Model: A Case Study of Nakhon Sawan Municipality in Thailand - Karn Chalermwongphan; Prapatpong Upala (My University, 2019)
Background: The present research aimed to compare and evaluate two forms of shared roadways, which were Conventional Bike Lane (CBL) and Median Bike Lane (MBL). Methods: The road network and traffic conditions of Nakhon Sawan Municipality, comprised of 712 links and 237 nodes, simulated by using the AIMSUN microscopic simulation software in order to compare the delay time, operating speed, total travel time, fuel consumption, and emission of carbon dioxide (CO 2 ), nitrogen oxide (NO X ), Particulate Matter (PM), and Volatile Organic Compounds (VOC). Results: The obtained results can be used as efficiency data for designing a campaign to encourage private car drivers to change their daily transportation mode to bicycle, which will ultimately help to solve traffic congestion problems and reduce environmental impacts in a sustainable way. The research results showed that a campaign encouraging a change in transportation mode should focus on reducing 36 percent of all private cars in the road network (at least 9,691 veh/hr). Conclusion: This approach will minimize the delay time in the road network by 0.89 sec/km and reduce 1,228.66 liters of fuel consumption, 2,769,764.47 g/km of carbon dioxide, 8654.86 g/km of nitrogen oxide, 1,463.33 g/km of particulate matter, and 1,383.93 g/km of volatile organic compounds.
Keywords: Traffic count; Sustainable transport; Vehicle emissions and performance